Development of inexpensive perovskite Mn‐based oxygen carriers using the waste manganese sand for chemical looping gasification. (29th September 2020) - Ren, Tian; An, Mei; Hu, Xiude; Ma, Jingjing; Guo, Qingjie
Summary: Perovskite materials have been proven to be promising oxygen carriers in chemical looping gasification(CLG). To apply the perovskite oxygen carriers commercially, it is necessary to discover inexpensive, abundant reserves as well as environmentally friendly raw materials. In this study, the waste manganese sand filter material from a water treatment process was reused as a novel Mn source and combined with Ca(OH)2 to produce perovskite oxygen carrier. The performance of the perovskite oxygen carrier using the waste manganese sand filter material was compared with the perovskite oxygen carrier using the manganese ore at the same experiment conditions. The experiments were performed in a thermogravimetric analyzer (TG‐DSC) and a batch fluidized‐bed reactor. The results indicated that under the same oxygen carbon ratio, when the two oxygen carriers react with coal respectively, the Ca(OH)2 /waste manganese sand filter material can release 1151 J/g more heat than the Ca(OH)2 /manganese ore. Furthermore, the catalytic effect on the coal gasification of the Ca(OH)2 /waste manganese sand filter material was shown to be the best when the carbon conversion between 0.4 and 0.8. Both Mn‐based pervoskite oxygen carriers released gaseous oxygen under an inert atmosphere at 950°C, whereas the Ca(OH)2 /waste manganese sand filter material showed higher gaseous oxygen release rate. Cyclic redox tests of the two Mn‐based perovskite oxygen carriers over 20 cycles showed that the Ca(OH)2 /waste manganese sand filter material behaved steadily with a higher syngas yield and attrition resistance beingachieved. Therefore, the perovskite oxygen carriers produced from the waste manganese sand filter material could potentially be used as an inexpensive and promising oxygen carrier in the CLG process of coal. Abstract : This study proposes the reuse of the waste manganese sand filter material as a novel Mn source to produce inexpensive perovskite oxygen carriers, which not only realizes the utilization of waste materials, but also significantly reduces the development cost of oxygen carriers. Experimental studies showed the perovskite oxygen carrier produced from the waste manganese sand filter material had a better reactivity and attrition resistance in comparison with the perovskite oxygen carrier produced from the manganese ore at the same experiment conditions.